A Potential Role for Robotic Cholecystectomy in Patients with Advanced Liver Disease: Analysis of the NSQIP Database. Issue 4 (April 2020) - Aziz, Hassan; Zeeshan, Muhammad; Kaur, Navpreet; Emamaullee, Juliet; Ahearn, Aaron; Kulkarni, Sujit; Genyk, Yuri; Selby, Robert R.; Sheikh, Mohd Raashid
Robotic surgery has been widely adopted by many specialties, including hepatobiliary surgery. However, robotic procedures generally require longer operative times and are costlier than their laparoscopic counterparts. The role for robotic cholecystectomy (RC), particularly in patients with advanced liver disease, has not been established. A retrospective analysis of the NSQIP database was performed, focusing on patients with chronic liver disease who underwent cholecystectomy. Patients were categorized based on their model for end-stage liver disease (MELD) score and the type of surgical procedure: open, laparoscopic, or RC. Rates of a variety of postoperative complications including length of stay (LOS) were analyzed. In patients with a MELD score of 21 to 30, open cholecystectomy was associated with a long hospital LOS (3 vs 1 vs 1; P 20.01). RC was equivalent to laparoscopic cholecystectomy in terms of perioperative mortality for higher MELD score patients but was associated with lower conversion rates and overall LOS. This data suggests that RC should be considered in patients with advanced liver disease needing cholecystectomy.